PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X SMA NEGERI 2 KUNINGAN TAHUN AJARAN 2021/2022 (JGuruku: Jurnal Penelitian Guru, 2023)
This research was conducted at SMAN 2 Kunungan with the type of research namely "Classroom Action Research". The research was conducted to improve students' speaking skills, especially retelling biographical texts using the Numbered Head Together (NHT) type cooperative learning model, using object class X MIPA 7 totaling 36 students, the learning process consisted of two cycles, each cycle consisting of 3 meeting, twice for the learning process and 1 meeting for the test. The results of Classroom Action Research in the first cycle, in general, students can participate in the learning process, but in speaking skills, the lowest score is 50 and the highest is 85, and the average score is 65.7 and the KKM is 75. Based on the analysis, the research Class action in the second cycle has increased, as evidenced by the value of students' speaking skills which have increased, namely all students have reached KKM in basic competency skills. Based on the results of the comparison of values between the first cycle and the second cycle, learning completeness in the second cycle reached 94%.